Sustaining grouper populations: eafm-based evaluation in the marine ecosystem of Sabang, Aceh - Miswar, Edy; Rahmah, Alvi; Mutia Aprilla, Ratna; Agustina, Imelda; Salmarika, Salmarika; Khairani, Khairani (Depik, 2025)
Sabang as the westernmost region of Indonesia and bordering the Indian Ocean and the Malacca Strait has fishery potential that must be maintained so that it is sustainable. Good management of grouper fish (Epinephelus sp.) resources is a solution so that fishery potential remains sustainable, one of which is the ecosystem approach. So far, many studies related to grouper management based on an ecosystem approach have been carried out in several regions in Indonesia, but none have focused on fisheries in Sabang. Therefore, this study aims to assess the status of grouper resource management, provide management recommendations and disseminate the results of the assessment of grouper resource management status in Sabang. This research was conducted from July to August 2022, located in Sabang, Aceh. Observation and direct interviews were conducted to collect the data and then analyzed by a multi-criteria analysis with composite index development. Based on the value of these indicators, it shows that the domain of grouper fish resources in Sabang caught using the hand line is good category with a green flag model and a composite value of 82. This means that the management of grouper fish resources in Sabang has not been running optimally. So, it is necessary to improve fisheries management in several aspects to support sustainable fisheries management.Keywords:GrouperEAFMSabangFisheriesSustainability